2020
DOI: 10.1155/2020/2547902
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] miR‐30a‐5p Inhibits Proliferation and Migration of Lung Squamous Cell Carcinoma Cells by Targeting FOXD1

Abstract: Objective. To investigate the mechanism of miR-30a-5p inhibiting proliferation and migration of lung squamous cell carcinoma (LSCC) cells by targeting FOXD1. Methods. Bioinformatics was used to analyze differentially expressed genes in the TCGA_LUSC database. qRT-PCR was used to detect the expression levels of miR-30a-5p and FOXD1 in human normal lung epithelial cell line and human LSCC cell lines. The protein expression of FOXD1 was detected by western blot. The cell viability and colony formation abilities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…On this basis, this study revealed that miR-30a-5p may modulate ANLN in LUAD. Inactivated miR-30a-5p was discovered in different types of cancer including breast cancer [31], lung squamous cell car-cinoma [32], oral carcinoma [33], and clear cell renal cell carcinoma [34] and could work as a cancer suppressor. The present investigation illustrated evidently restrained miR-30a-5p in LUAD and its targeting ANLN.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, this study revealed that miR-30a-5p may modulate ANLN in LUAD. Inactivated miR-30a-5p was discovered in different types of cancer including breast cancer [31], lung squamous cell car-cinoma [32], oral carcinoma [33], and clear cell renal cell carcinoma [34] and could work as a cancer suppressor. The present investigation illustrated evidently restrained miR-30a-5p in LUAD and its targeting ANLN.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, miR-139-5p was downregulated in LUAD and exerted the ability to inhibit proliferation, migration, and invasion of cancer cells by targeting MAD2L1 [ 37 ]. Moreover, several studies have found that miR-30a-5p inhibited the proliferation of multiple cancers, such as breast cancer, glioma, and lung squamous cell carcinoma [ 38 40 ]. It is reported that miR-490-3p overexpression significantly inhibited the proliferation, invasion, and migration of hepatocellular carcinoma cells by activating BCYRN1 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that FOXD1 plays a oncogenic effect in several types of cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and likely associates with the mechanism for radioresistance [ 37 ]. In this study, our data showed that FOXD1 is capable of directly regulating the expression of G3BP2 , which is capable of inhibiting p53 activity through a direct binding, which may further promote p53 nuclear export via increasing p53 sumoylation [ 38 ] and serves as a poor prognostic marker in prostate cancer patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%